2020
DOI: 10.4251/wjgo.v12.i9.1014
|View full text |Cite
|
Sign up to set email alerts
|

γ-glutamyl transferase-to-platelet ratio based nomogram predicting overall survival of gallbladder carcinoma

Abstract: BACKGROUND Gallbladder carcinoma (GBC) carries a poor prognosis and requires a prediction method. Gamma-glutamyl transferase–to–platelet ratio (GPR) is a recently reported cancer prognostic factor. Although the mechanism for the relationship between GPR and poor cancer prognosis remains unclear, studies have demonstrated the clinical effect of both gamma-glutamyl transferase and platelet count on GBC and related gallbladder diseases. AIM To assess the prognostic value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…A recent study has revealed that a high GPR is associated with poor survival of patients with cancer [40]. Our meta-analysis of 10 studies including 4706 patients also found that HCC patients with high GPR had shorter OS, RFS, and DFS than those with low GPR.…”
Section: Discussionsupporting
confidence: 69%
“…A recent study has revealed that a high GPR is associated with poor survival of patients with cancer [40]. Our meta-analysis of 10 studies including 4706 patients also found that HCC patients with high GPR had shorter OS, RFS, and DFS than those with low GPR.…”
Section: Discussionsupporting
confidence: 69%
“…The risk factors for eCCA include primary sclerosing cholangitis, smoking, and heavy alcohol drinking [ 2 , 3 ]. In contrast, GBC is one of the most common malignancies of the digestive system, accounting for approximately 1% of all cancers and 80–95% of all eBTCs [ 4 ]. The main causes of GBC are gallstones and chronic cholecystitis and can therefore easily be confused with them due to similar symptoms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Revealing residual disease in the specimen of the second operation after incidental discovery of GB carcinoma with cholecystectomy predicts worse prognosis, despite the achievement of R0 resection[ 160 ]. The ratio of γ-glutamyl transferase to platelet count may predict GB carcinoma patient survival and was included in a relevant nomogram[ 161 ]. There are several prognostic scoring systems and nomograms predicting survival[ 162 - 166 ] or lymph node metastases[ 167 ].…”
Section: Prognosismentioning
confidence: 99%